SELF-ASSESSMENT OF COMMUNICATION SKILLS OF HEALTHCARE PROFESSIONALS: A QUANTITATIVE STUDY - Skarbalienė, Aelita; Skarbalius, Egidijus; Gedrimė, Lina; Rapolienė, Lolita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Communication and social skills are becoming increasingly valuable in the 21st century. Despite increasing awareness of the importance of communication skills in modern healthcare practice, there is a lack of research that addresses this issue. The aim of this research is to assess the communication skills of healthcare professionals working in Lithuanian healthcare institutions. Respondents (n=1154) were asked to assess their own communication skills using the Interpersonal Communication Skills Inventory. The research revealed that sending clear message skills were the strongest and giving/getting feedback skills were the lowest for most of the respondents, including physicians, head nurses, nurse, nurse assistants, and other personnel. The strongest aspects were that respondents can talk to other people and others seemed to be interested and attentive when healthcare specialists were talking because in conversation they were trying to talk about things of interest to both them and the other persons. The respondents could recognize as well how others were reacting to what they were saying. However, they did not always care how other person feels about the point they try to make. Emotional interaction skills were the lowest for most of the respondents in this study. They saw a tendency to change the subject when other person’s feelings enter into the discussion and it was difficult for them to think when they were angry with someone. It was summarized that talking, listening, and emotional interaction skills of the respondents are the areas that need more consistent attention, and giving / getting feedback is the skill that needs much improvement.